2008
DOI: 10.1007/s11581-008-0280-6
|View full text |Cite
|
Sign up to set email alerts
|

Ionic conductivity studies of 49% poly(methyl methacrylate)-grafted natural rubber-based solid polymer electrolytes

Abstract: The potential of 49% poly(methyl methacrylate)-grafted natural rubber (MG49) as a solid polymer electrolyte film in rechargeable batteries system were explored. The flat, thin, and flexible films were prepared by solution casting technique. The ionic conductivity was investigated by alternating current impedance spectroscopy. The highest conductivity of 2.3 × 10 −7 Scm −1 was obtained at 20wt.% of LiBF 4 salts content, while 4.0 × 10 −8 Scm −1 was obtained at 15wt.% LiClO 4 salts loading. The observation on st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 11 publications
4
27
2
Order By: Relevance
“…This phenomenon resulted in low electrolyte conductivity to be applied in electrochemical devices even though the addition of lithium salt reaches its maximum level [31]. Nevertheless, this finding was similar to the finding reported elsewhere in which the high ionic conductivity still occurs either by the reduction of crystalline phase or the enhancement of amorphous phase in the polymer host [22,24,29,31].…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…This phenomenon resulted in low electrolyte conductivity to be applied in electrochemical devices even though the addition of lithium salt reaches its maximum level [31]. Nevertheless, this finding was similar to the finding reported elsewhere in which the high ionic conductivity still occurs either by the reduction of crystalline phase or the enhancement of amorphous phase in the polymer host [22,24,29,31].…”
Section: Resultssupporting
confidence: 87%
“…Despite the fact that the highest conductivity achieved by this electrolyte at this point, the value is still low to be applied in electrochemical devices as compared to the conventional system. However, this finding is the highest ionic conductivity at room temperature obtained in comparison to our previous studies on the series of MG49 [31], (70:30) MG49-PMMA [39], and (30:70) MG49-PMMA-LiClO 4 [23] blended solid polymer electrolytes. This result indicated that the increase in ionic conductivity was due to the increase of PMMA content.…”
Section: Resultscontrasting
confidence: 55%
See 2 more Smart Citations
“…Ionic conductivity MG49 without salt is 1.0 10 -12 S cm -1 and the highest conductivity is 2.3 10 -7 S cm -1 at 20 wt. % of LiBF 4 salt addition as reported by our preliminary study on MG49 film [17]. After blending with 50% PMMA, MG49 without salt possess the conductivity of 1. ]…”
Section: Ionic Conductivity As Well As [O/limentioning
confidence: 71%